OBJECTIVE COMPOSITION OF LEGALIZATION OF ILLEGAL INCOME. SUBJECT OF ACTION. BENEFIT HAVING PROPERTY VALUE, MATERIAL VALUES, BANKROLL, PROPERTY AS THE SUBJECT OF CRIME - Girogi Shashiashvili (European Scientific Journal, ESJ, 2013)
It is essential to define the subject of crime as the right qualification of legalization depends on it. The issue related to the subject of crime is disputable in the theory of criminal law as well as among practitioners of different countries of the world. To clarify this issue first of all should be discussed those types of phenomena that are defined in the theory and international practice as the forms of crime.